Cross-Country Comparisons of Disability and Morbidity: Evidence from the Gateway to Global Aging Data. (4th December 2017) - Lee, Jinkook; Phillips, Drystan; Wilkens, Jenny; Chien, Sandy; Lin, Yu-Chen; Angrisani, Marco; Crimmins, Eileen
Abstract: Background: International comparisons of disease prevalence have been useful in understanding what proportion of disease might be preventable and in informing potential policy interventions in different cultural and economic contexts. Using newly available, harmonized data from 20 countries, we compare disability and morbidity of older adults between the ages of 55 and 74. Methods: The Gateway to Global Aging Data, a data and information portal, provides access to easy-to-use individual-level longitudinal data from 10 surveys covering over 30 countries. Exploiting harmonized measures available from the Gateway, we descriptively examine how disability and morbidity differ across countries. Results: Significant cross-country differences are observed for several health indicators. Comparing countries with the highest and lowest prevalence rates, we observe that hypertension rates vary twofold and stroke rates vary threefold, while disability and arthritis rates vary more than fivefold. Among women, higher gross domestic product and life expectancy are related to lower diabetes, heart disease, and better functioning. Among men, national indicators of economic conditions are not significantly associated with reported disease prevalence. Conclusions: We document substantial heterogeneity in disability and morbidity across countries, separately for men and women and after controlling for population age composition and education. Rich data from various surveys across the world offers remarkable opportunities for cross-country analyses, calling for further investigation of what drives observed differences. The Gateway to Global Aging Data provides easy-to-use harmonized data files and tools to facilitate this type of research.